PSIKOLOGI PERKEMBANGAN BERDASARKAN TUJUH HUKUM PSIKOLOGI PERKEMBANGAN PADA REMAJA DI SMA N 1 TIGALINGGA - Dorlan Naibaho; Farisca Lumbantobing; Eunike Perdana T; Exaudi Sitanggang (CV. Denasya Smart Publisher, 2024)
Apart from babies and children, teenagers also need special attention because teenagers are transitional adults from children to adults. Teenagers need guidance and direction so that developmental psychology based on the seven developmental psychology experiences experienced by teenagers can develop. The ultimate goal of this research is to provide information for all parties regarding developmental psychology, namely the development that occurs in individuals from infancy to adulthood, knowing what problems or obstacles individuals experience in the development process based on the principles of developmental psychology from infancy to adulthood and challenges. faced. This research uses a qualitative research method.